A facile synthesis of Ag/AgCl hybrid nanostructures with tunable morphologies and compositions as advanced visible light plasmonic photocatalysts. Issue 22 (12th May 2016) - Shahzad, Aasim; Kim, Woo-Sik; Yu, Taekyung
Abstract : Ag/AgCl plasmonic photocatalysts are synthesized by a simple and rapid method in an aqueous-phase. The Ag/AgCl hybrid nanostructures exhibited enhanced photocatalytic activity and stability toward the degradation of methyl orange under visible light irradiation because of their strong surface plasmon resonance (SPR) effect. Abstract : This paper describes a simple and fast aqueous-phase route to the synthesis of Ag/AgCl hybrid nanostructures. These hybrid nanostructures were synthesized by reduction of AgCl nanoparticles with controlled shapes prepared by reacting Ag + with Cl − in the presence of polyethyleneimine (PEI) in an aqueous-phase. We could easily control the morphology and composition of the nanostructures by varying the experimental conditions, including the reaction temperature and the amount of the reducing agent. The as-synthesized Ag/AgCl hybrid nanostructures exhibited enhanced photocatalytic activity and stability during the degradation of methyl orange under visible light irradiation because of their strong surface plasmon resonance (SPR) effect.